INTERJEKSI HA! DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK: PENDEKATAN SEMANTIK METABAHASA ALAMI - Dian Syaputra; Mulyadi Mulyadi (Balai Bahasa Sumatera Utara, 2022)
Interjection is a word used to express feelings or something spontaneously. In Indonesian there are many interjection words, but here what will be discussed is an interjection HA! which can be used in various spontaneous expressions. Not only that, Interjection HA! have similarities and differences with interjections in other Indonesian languages. This study aims to find the meaning of the Ha! which is used in the film